(untitled) (Bangladesh Journal of Botany, 2025)
Taking jujube from 13 counties of Lvliang City as the research object, the relationship between main nutrients and flavor characteristics of jujube was analyzed. The difference of flavoring potential of jujube in different counties was explored. Through correlation matrix analysis, principal component analysis, cluster analysis and regression analysis models, the results showed that sugars (sucrose, fructose and glucose) were the main contributing factors to sweetness. Acids (total acids) were significantly correlated with sour taste. Fat and protein show a nonlinear relationship in the influence of texture and flavor intensity. Specifically in terms of distribution area, the high-sugar jujube produced in Linxian County is suitable for the production of sweet food. The sugar content of jujube in Linxian County is 569.64 mg/g, the glucose content is 166.84 mg/g, and the fructose content is 175.75 mg/g, and its sweetness has obvious advantages. Xingxian jujube has high acidity and total acid content is 4.76 mg/g, which is suitable for developing functional sour food. The water content of jujube in Shilou County is 19.5%, the protein content of jujube in Liulin County is 3.59 g /100g, and the ash content of jujube in Fenyang City is 2.79g/100g. These three places are suitable for making functional food and high value-added products. This research provides technical support for the development of high-quality jujube products for sensory optimization and industrial development. Bangladesh J. Bot. 54(3): 571-579, 2025 (September)